2021
DOI: 10.3390/en14144295
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Efficiency Analysis of a System for Improving Fine-Coal Combustion Efficiency of Power Plant Boilers

Abstract: Hard coal is widely used as a source of energy, and a number of catalysts have been developed to minimize the noxious impact of this fuel on combustion. This paper presents the cost-efficiency analysis of a system for improving the combustion of solid fuels, especially fine coal, in power boilers. The system is provided with a control and supervision device. It has been designed for better accuracy in controlling the boiler operating parameters, with a view to improving combustion efficiency due to the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Compared with solid fossil fuels, the calorific value of the obtained torrefaction from goldenrod is similar. The calorific value of hard coal is 20.9–33.4 MJ∙kg −1 [ 54 , 55 , 56 , 57 ] and brown coal (lignite) 5.9–24.9 MJ∙kg −1 [ 58 , 59 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with solid fossil fuels, the calorific value of the obtained torrefaction from goldenrod is similar. The calorific value of hard coal is 20.9–33.4 MJ∙kg −1 [ 54 , 55 , 56 , 57 ] and brown coal (lignite) 5.9–24.9 MJ∙kg −1 [ 58 , 59 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of earlier tests, as described in [31,36], indicated that the use of a system designed to improve the energy efficiency of boiler systems is only cost effective for boiler capacities from 1 to 5 MW.…”
Section: Resultsmentioning
confidence: 99%
“…The system is designed to improve the efficiency of energy generation and distribution, resulting in reduced environmental emissions of harmful combustion products. Both the extra energy generated and the reduced emission of harmful compounds are the effects of the use of the modifier and of the fuel oil combustion system refurbishment, shown in [31,32,36].…”
Section: Resultsmentioning
confidence: 99%
“…Ziembicki et al [1] analysed heat recovery from combustion gases in heating plants using gaseous and liquid fuels. Tic and Guziałowska-Tic [2] investigated the cost-efficiency dependence of the combustion of solid fuel improvement in power boilers, especially fine coal.…”
Section: Introductionmentioning
confidence: 99%